Fetal teratomas – A retrospective observational single‐center study. (17th December 2020) - Simonini, Corinna; Strizek, Brigitte; Berg, Christoph; Gembruch, Ulrich; Mueller, Andreas; Heydweiller, Andreas; Geipel, Annegret
Abstract: Objective: Evaluation of course and outcome of pregnancies with prenatally diagnosed fetal teratomas of various locations in a single center between 2002 and 2019. Methods: Retrospective observational single‐center study including prenatally suspected or diagnosed fetal teratomas. Focus was put on ultrasound findings during pregnancy. Complications, need for intervention and outcomes were compared according to tumor location. Results: 79 cases of fetal teratomas were seen at our center between 2002 and 2019. Most frequent tumor locations were the sacrococcygeal region (59.5%), neck (20.2%) and oropharynx (7.6%). Complications mainly included polyhydramnios and cardiac compromise. Need for intervention during pregnancy was significantly higher in pericardial teratomas. Preterm birth before 37 and early preterm birth before 32 weeks occurred in 72.7% and 29.1%, respectively. Major causes of perinatal death were tumor bleeding in sacrococcygeal teratomas (SCTs) and respiratory failure in cervical and oropharyngeal teratomas. Conclusion: There is a high need for intervention in pregnancies complicated by fetal teratomas. Pericardiocentesis in pericardial teratomas is often inevitable to reduce the risk of intrauterine demise. Amniotic fluid drainage in associated severe polyhydramnios helps to reduce the risk of preterm birth, a major cause of additional morbidity and mortality. MRI in supplement to prenatal ultrasound is useful in fetal teratomas of the neck and oropharynx in order to plan delivery.